Beyond Meat: A Comparison of the Dietary Intakes of Vegetarian and Non-vegetarian Adolescents - Segovia-Siapco, Gina; Burkholder-Cooley, Nasira; Haddad Tabrizi, Sara; Sabaté, Joan (Frontiers in Nutrition, 2019)
Dietary intake of adult vegetarians from large prospective studies has been well-characterized but is rarely reported in vegetarian adolescents. Our objective was to describe and compare the dietary intake of vegetarian adolescents with their non-vegetarian counterparts in a population known to espouse healthy living. Adolescents (n = 534) aged 12–18 years old from middle and high schools near major Adventist universities in Michigan and Southern California provided dietary, demographic, and anthropometric data. Dietary intake was measured with a validated 151-item self-administered web-based food frequency questionnaire; weight and height were measured during school visits. Vegetarian was defined as the combined intake of meat, meat derivatives, poultry, and fish of < 1 serving per week. Descriptive statistics and ANCOVA were used to compare the intake of vegetarians and non-vegetarians. Vegetarians significantly ate more fruits, vegetables, and other plant-based foods, but significantly less foods of animal origin, sugar-sweetened beverages, and coffee/tea compared to non-vegetarians. Vegetarians had significantly higher intakes of carbohydrates and total protein but lower intakes of fats, animal protein, and zinc compared to their counterparts. A majority (75% or more) of both groups met the 2015 Dietary Guidelines’ age-and-gender-specific recommendations for most nutrients but only 16–18% of vegetarians/non-vegetarians did not exceed the upper limit for sodium. More vegetarians (49%) than non-vegetarians (25%) had <10% of their caloric intake from SFA. More than 90% of both groups met dairy recommendations, but greater proportions of vegetarians met recommendations for vegetables, fruits, nuts/soy products, and legumes than non-vegetarians. Of the non-vegetarians, only 7% and 44% met the fish and meats/poultry/eggs recommendation, respectively, which none of the vegetarians met. Compared to the general US adolescent population, both diet groups ate more fruits, vegetables, dairy and protein foods, and also consumed more micronutrients but less macronutrients. Overall, vegetarian adolescents have a more favorable dietary intake profile than non-vegetarians, but both vegetarians and non-vegetarians in this study population have a more adequate diet than the general US adolescent population. The influence of the Adventist plant-based diet culture that is translated both at home and at school is evident in our findings.